Nonlinearities in Economic Globalization Effects on the Environment: New Insights from a Panel Smooth Transition Regression Model - Çiğdem Demir Toker; Metehan Ercan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractThis study aimed to estimate the impact of economic globalization on environmental quality and examine the role of renewable energy production (REP) in this impact. For this purpose, the annual data of 1976–2021, which is the longest possible period, of the top 5 countries (Sweden, Switzerland, Norway, France, and Denmark) that show the best performance according to the Global Green Economy Index 2022 report, were used. These countries were chosen due to their high performance in green economy integration; and thus, it was considered that this research could provide reference results for other countries. In order to achieve this, the panel smooth transition regression model was applied to the dataset. This nonlinear approach divides the series into homogeneous regimes depending on the threshold variable and allows us to make regime-specific interpretations. As a result, this study, in which REP was defined as the threshold variable, has shown that there is a two-regime nonlinear relationship between environmental quality and economic globalization. According to the findings, economic globalization caused an increase in environmental degradation in the first regime, which had low REP. However, this impact was eliminated in the second regime, where REP was high.